Producción audiovisual en género documental para la difusión de la nacionalidad Siona en la parroquia Puerto Bolívar, cantón Putumayo, provincia de Sucumbíos período 2023-2024 - Vargas Esparza, Jiniffer Lizbeth (2024)
Ecuador's cultural diversity is reflected in the richness of its indigenous nationalities, with the Siona, located in the Puerto Bolívar parish of Putumayo canton in Sucumbíos province, standing out. This nationality possesses profound ancestral knowledge and a close relationship with nature but faces significant challenges in preserving its culture due to globalization and modernization. Audiovisual production, especially in the documentary genre, emerges as a powerful tool for making the Siona culture visible and promoting it. The main objective of this thesis project is to create a documentary that contributes to the dissemination of the traditions and culture of the Siona nationality, promoting its preservation and recognition.